2014
DOI: 10.1016/j.cnsns.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state, self-oscillating and chaotic behavior of a PID controlled nonlinear servomechanism by using Bogdanov–Takens and Andronov–Poincaré–Hopf bifurcations

Abstract: Please cite this article as: Pérez-Molina, M., F.Pérez-Polo, M., Steady-state, self-oscillating and chaotic behavior of a PID controlled nonlinear servomechanism by using Bogdanov-Takens and Andronov-Poincaré-Hopf bifurcations, Communications in Nonlinear Science and Numerical Simulation (2014), doi: http://dx.doi.org/ 10. 1016/j.cnsns.2014.03.003 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This codimension-two bifurcation has been found and studied in a large number of systems considered in different fields (see, for instance, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This codimension-two bifurcation has been found and studied in a large number of systems considered in different fields (see, for instance, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Although parameters of the PID controller can be adjusted manually when the motor is running, it cannot guarantee robustness if the external loading changes dramatically. Pérez-Molina and Pérez-Polo (2014) studied the nonlinear dynamics of a PID controlled DC servomechanism under constant torque and random noise. Even though it was demonstrated that the chaotic behavior of the system could be used corporately with the PID controller to reach the desired set point, accuracy and practicability of the proposed methodology under complex working conditions remain an issue.…”
Section: Introductionmentioning
confidence: 99%